2013
DOI: 10.5337/2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Glacier systems and seasonal snow cover in six major Asian river basins: hydrological role under changing climate

Abstract: The publications in this series cover a wide range of subjects-from computer modeling to experience with water user associations-and vary in content from directly applicable research to more basic studies, on which applied work ultimately depends. Some research reports are narrowly focused, analytical and detailed empirical studies; others are wide-ranging and synthetic overviews of generic problems.Although most of the reports are published by IWMI staff and their collaborators, we welcome contributions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 88 publications
2
21
0
Order By: Relevance
“…Additionally, early seasonal snow-melt may also expose clean glacier ice, which can produce more melt during the summer months than the more airy snow. A decline in snow-cover has been observed by Savoskul and Smakhtin [58] in the Kabul basin between the periods 1960-1990 and 2000-2010. This decline in snow-cover expedited glacier-melt and resulted in a shrinking glacier length.…”
Section: Future Discharge and Flood Frequencymentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, early seasonal snow-melt may also expose clean glacier ice, which can produce more melt during the summer months than the more airy snow. A decline in snow-cover has been observed by Savoskul and Smakhtin [58] in the Kabul basin between the periods 1960-1990 and 2000-2010. This decline in snow-cover expedited glacier-melt and resulted in a shrinking glacier length.…”
Section: Future Discharge and Flood Frequencymentioning
confidence: 97%
“…Other studies e.g., [59][60][61][62] observed shrinkage in glacier length in the Hindukush region (including the Kabul basin). Early seasonal snow-melt and exposure of glacier ice, which resulted in a negative glacier mass balance (about −0.3 ± 0.1 m water equivalent per year based on 2003-2008 data analysis by Kääb et al [63] and Kääb et al [64], likely have supported part of the rising flows during peak summer months in the recent decades [58,65]. However, since the glacier length in the Kabul basin declined as per Randolph Glacier Inventory 5.0 data [66] to only 2.2% of the total basin area (approximately 2100 km 2 ), its contribution to rising flows are probably small.…”
Section: Future Discharge and Flood Frequencymentioning
confidence: 99%
“…An accurate understanding of the relative importance of snowmelt and glacial melt in various river basins of HKH-TP is an important and fundamental problem in hydrology within the context of climate change and water resources management and planning in a changing climate (Schaner et al, 2012). On the other hand, assessments and quantifications of the contributions that seasonal snows and glaciers make separately to river runoff is a challenging problem (Armstrong, 2010;Savoskul and Smakhtin, 2013;Lutz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Upper Indus Basin is one of the most melt water dependent river basins in the world. Savoskul and Smakhtin (2013) have made a broad assessment to approximate the contributions of glacial melt and seasonal snowmelt in six major river basins of the HKH-TP region. Their approach has been a synthesis of previously published glacial mass budget estimates and snowmelt models based on temperature-index methods to arrive at estimates of specific glacier runoff in the catchments where such studies are available.…”
Section: Introductionmentioning
confidence: 99%
“…Immerzeel et al (2010) pointed out that the melt water is extremely important in the Indus and Brahmaputra rivers but only plays a modest role for the Ganges, Yangtze, and Yellow rivers in Asia. Savoskul and Smakhtin (2013) analyzed six major Asian river basins (Indus, Ganges, Brahmaputra, Amu Darya, Syr Darya, and Mekong) and indicated that the glacier melt contribution to river runoff varies significantly. Lutz et al (2014) rivers of Indus, Ganges, Brahmaputra, Salween, and Mekong.…”
Section: Introductionmentioning
confidence: 99%